2019
DOI: 10.1063/1.5109069
|View full text |Cite
|
Sign up to set email alerts
|

Photon helicity driven surface photocurrent in CuSe films

Abstract: We report excitation of the spin-polarized currents in CuSe nanocrystalline films and demonstrate that the inversion of the excitation photon helicity reverses the direction of the photocurrent propagating perpendicular to the plane of incidence. By performing measurements of the photocurrent propagating both along and perpendicular to the plane of incidence, we show that the observed spin-polarized currents originate from the circular surface photogalvanic effect (C-SPGE). In contrast to the conventional circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
1
5
0
2
Order By: Relevance
“…Our experiments show that in the studied CuSe/t-Se film, the dependences of the photovoltage on the polarization and incidence angle of the excitation beam well correspond to those reported in polycrystalline CuSe 31 and CuSe/amorphous Se 32,33…”
Section: Please Cite This Articlesupporting
confidence: 82%
See 1 more Smart Citation
“…Our experiments show that in the studied CuSe/t-Se film, the dependences of the photovoltage on the polarization and incidence angle of the excitation beam well correspond to those reported in polycrystalline CuSe 31 and CuSe/amorphous Se 32,33…”
Section: Please Cite This Articlesupporting
confidence: 82%
“…[21][22][23] This second-order nonlinear optical phenomenon, which was experimentally studied in 22,24,25 , can be observed in 2D layered materials, along with other nonlinear optical effects. [26][27][28][29][30] We have recently demonstrated that the SPGE dominates the photoresponse of the semitransparent stoichiometric CuSe 31 and nanocomposite CuSe/Se films. [32][33][34] In the transverse configuration, when the photocurrent at the irradiated interface flows perpendicular to the incidence plane, both linear and circular SPGE photocurrents are permitted by the symmetry.…”
mentioning
confidence: 99%
“…The theory of the SPGE has been developed in references [2,7,8]. Experimentally SPGE has been demonstrated in gallium arsenide [9], copper crystal [6], and CuSe films [10,11]. Usually, SPGE is accompanied by the PDE and bulk photogalvanic effect (for example, see references [6,12,13]).…”
Section: Introductionmentioning
confidence: 99%
“…The preparation and characterization of binary [1][2][3][4][5][6], ternary [7][8][9][10], quaternary [11][12][13] and pentanary thin films [14][15][16][17][18] have been reported. In general, these films are produced using various physical and chemical deposition techniques [19], each having its own advantages and limitations.…”
Section: Introductionmentioning
confidence: 99%